Director Human Capital, Information Processing Demands, and Board Effectiveness - Khanna, Poonam; Jones, Carla D.; Boivie, Steven (Journal of Management, 2014)
Research on human capital as a source of competitive advantage has focused largely on firm employees. In this article, we argue that outside directors’ general human capital can also be a source of competitive advantage. Firm performance is likely to benefit from directors’ human capital—that is, their prior experience and education—because such human capital is likely to make them more effective at monitoring management and providing advice. Drawing on insights from research on individuals’ cognitive limitations, we further argue that the extent to which the firm is able to benefit from this human capital can be severely limited by the demands for information processing that directors face from their other board positions. Consequently, we find that the benefit of directors’ human capital is contingent upon the information processing load placed upon them from their other board appointments. We find support for our hypotheses using data on over 5,700 directors from 650 firms sampled from the Fortune 1000. This study extends the nascent literature on board human capital by showing that in addition to specific expertise in relevant areas, directors’ general human capital can also help firms create competitive advantage. The theory developed in this article also contributes to the literature on strategic human capital by incorporating the concept of information processing demands, suggesting that not only do such demands leave limited cognitive capacity for directors to focus on the focal firm but also that they can severely diminish the beneficial effects of directors’ general human capital.